CONSUMER'S CONSIDERATION IN CHOOSING A HOSPITAL - retnaningtyas, sri; Hariyanti, Tita; Rasyid, Harun Al (Jurnal Aplikasi Manajemen, 2017)
The purpose of the research is to find out the consumers'consideration in choosing a hospital. The researcher utilizes the approach by measuring the impact of motivation, reference group, and marketing mix toward consumers'decision to choose An-Nisaa' hospital. The research is a quantitative by applying cross sectional study. Then, the researcher needs for about two months to take 70 respondents, which are taken from outpatients of polyclinic and An-Nisaa'Hospital by utilizing questionnaire as a research instrument. By the research, the researcher applies independent and dependent variables. The independent variable consists of motivation, reference group, and marketing mix. The dependent variable consists of consumers'decision to choose An Nisaa Hospital. The data analysis applies doubled linear analysis by using SPSS program. The result of the research shows that there is a simultaneous effect of motivation, reference group, and marketing mixed toward consumers'decision in choosing An-Nisaa'Hospital. Marketing mixed has a dominant influence. However, motivation partially has no effect toward consumers'decision in choosing An-Nisaa'Hospital.